Marketing Strategy on Tourism of Cultural Heritage (Case Study at the Heritage Palace in Sukoharjo Regency, Central Java) - Hasanah, Siti Nur; Suranto, S (Universitas Muhammadiyah Surakarta, 2022)
This study aims to depict the marketing strategy implemented by The Heritage Palace in increasing sales and to describe the constraints and solutions applied by The Heritage Palace in marketing activities. This type of research is qualitative with a case study research design. Research sources were managers, employees, and tourists of The Heritage Palace. Data collection methods used in this study were interviews, observation, and documentation. The validity of the data in this study employed the source and method triangulation. The data analysis technique utilized interactive analysis in three stages, namely data reduction, data presentation, and conclusion and verification. The results of this study indicated that the marketing strategy used by The Heritage Place in increasing sales was to determine the price according to the facilities obtained and conduct promotions by utilizing social media, newspapers, and television and collaborating with tour and travel agents. Heritage Place also had a constraint in performing marketing activities in the pandemic condition that made the government issue regulations to temporarily close tourist attractions. From this constraint, The Heritage had a solution to overcome problems by monitoring and evaluating the situation. These solutions make Heritage Place easier to make decisions to conduct marketing strategies according to government regulations that shift during the pandemic.